An EMG profile of lower limb muscles during linear glide and standing shot putting - Howard, R. M.; Conway, R.; Harrison, A. J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to provide a descriptive analysis of the phasic muscle activity of 8 lower limb muscles during performance of the shot put field event in track and field athletics. Six shot putters performed 3 standing and 3 full linear glide technique throws. Electromyography (EMG) of 8 lower limb muscles was recorded during the trials and the distance thrown was also measured. A comparison between standing and glide techniques are important from a coaching perspective. An increase in peak muscle activity of the Rectus Femoris was observed between the glide and standing throw, all other lower limb muscles showed no significant increases between the techniques. Results show significant increases between performances of standing and glide throws in female athletes however the mean differences were smaller in the male athletes.